2019
DOI: 10.3389/fimmu.2019.01433
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 Gain-of-Function Mutations Cause High Total STAT1 Levels With Normal Dephosphorylation

Abstract: Signal transducer and activator of transcription (STAT1)1 gain of function (GOF) pathogenic variants have been associated with increased levels of phosphorylated STAT1 and STAT1-dependent cellular responses. Delayed dephosphorylation was proposed as the underlying mechanism leading to the characteristically raised pSTAT1 levels. We examined the levels of STAT1 protein and message as well as rates of STAT1 phosphorylation, dephosphorylation, and degradation associated with STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 25 publications
7
58
0
Order By: Relevance
“…We demonstrated that different mutations, associated with STAT1 GOF, result in a STAT1 GOF phenotype via distinct mechanisms using real-time imaging and tracking of GFPtagged proteins. Our results (summarized in Table 1) are in line with previous reports (50)(51)(52), indicating that different molecular mechanisms can result in a STAT1 GOF phenotype. It remains unknown whether these differences (altered nuclear mobility, increased DNA binding, or increased nuclear import) are biologically relevant in influencing the patients' phenotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that different mutations, associated with STAT1 GOF, result in a STAT1 GOF phenotype via distinct mechanisms using real-time imaging and tracking of GFPtagged proteins. Our results (summarized in Table 1) are in line with previous reports (50)(51)(52), indicating that different molecular mechanisms can result in a STAT1 GOF phenotype. It remains unknown whether these differences (altered nuclear mobility, increased DNA binding, or increased nuclear import) are biologically relevant in influencing the patients' phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Fujiki et al (50) studied the R274Q mutation, reporting an impaired dephosphorylation for this mutant. Finally, Zimmerman et al (52) included monocytes from 14 STAT1 GOF patients, of whom 1 bearing the R274W and 2 the R274Q mutant. They observed a similar dephosphorylation rate for the pooled GOF mutants compared with the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies in patient samples found STAT1 itself to be elevated, suggesting that total STAT1, rather than pSTAT1, is the primary disease driver of STAT1 GOF. 58,59 In our current study, pSTAT1 was elevated in all GOF mutants following stimulation (as described in patients). In addition, increased total STAT1 was clearly seen in one GOF mutant, with a trend toward increased total STAT1 in two others.…”
Section: Discussionsupporting
confidence: 73%
“…Delayed dephosphorylation of STAT1 in these patients impairs the function of IL-6 and IL-21, thus decreasing STAT3-dependent differentiation of naïve CD4 + T cells into Th17 cells (20). Of note, a recent report suggests that some STAT1 GOF mutations may cause STAT1 levels to be high, although phosphorylation is normal (21). Disease severity appears to vary according to the mutation.…”
Section: Stat1 Gain Of Functionmentioning
confidence: 99%